Dominica : Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2004)
Poverty in Dominica exhibits the following: poor households tend to be larger than nonpoor households; poor households contain proportionately fewer persons of working age, and there is no significant difference in the gender distribution of poverty in the country. The challenges of this poverty-reduction strategy will be to foster growth and private sector employment, and to achieve fiscal and broader economic stability and a dynamic, accountable, and effective public service to provide a strong basis for the sustainable and integrated political, social, and economic development of Dominica.